Pengembangan Modul Fisika Berbasis Discovery Learning (Dl) Pada Pokok Bahasan Keseimbangan Dan Dinamika Rotasi - Nabila Unanti; Endang Lovisia (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to develop a physics based discovery learning (DL) module on the subject of balance and dynamics of rotation which is valid and practical. The problems in this research are 1) how to develop a physics module based on discovery learning (DL) on the subject of balance and rotation dynamics of student in class XI of SMA Negeri 2 reference Muara Beliti. 2) how are the characteristics of the physics module based on discovery learning (DL) to fulfill the goals of validity and practicality on the subject of balance and rotation dynamics of student in class XI SMA Negeri 2 reference muara beliti. The subject in this study were class XI MIPA 3 SMA Negeri 2 reference muara beliti which consisted of 9 students who were taken by purposive sampling technique. The develop of this research uses a four-D model consisting of define, design, develop and dessimination. The data was collected by using a student response questionnaire technique. And validation consists of 3 expert validations, material validation with an assessment of 37 in the good category, language validation with an assessment of 18 in the good category, and media validation with an assessment of 27 in the good category. Validation carried out to get results with an assessment of 82 in the good category. Students responses to the physics module based on discovery learning with an assessment of 33 in the very good category. So it can be said that the physics module based on discovery learning thet has been developed is valid and pratical